Iron deficiency and anemia in male and female adolescent athletes who engage in ball games - Nicotra, D.; Arieli, R.; Redlich, N.; Navot-Mintzer, D.; Constantini, N. W. (Journal of Clinical Medicine, 2023)
The aim of this study was to assess the prevalence of iron deficiency (ID) and iron deficiency anemia (IDA) among male adolescent athletes who participate in non-calorie-restricting sports, and to compare the results with female athletes of the same age and sports. Data of the hemoglobin concentration (Hb) and serum ferritin (sFer) levels of male (n = 350) and female (n = 126) basketball and football players, aged 11-18, from two sport medicine centers in Israel were gathered and analyzed. Mild ID was defined as sFer = 30 µg/L, moderate as sFer = 20 µg/L, and severe as sFer = 10 µg/L. IDA was defined as sFer = 20 µg/L and Hb < 13 g/dL for males and sFer = 20 µg/L and Hb < 12 g/dL for females. The prevalence of mild ID was 41.1% and 53.2%, moderate was 17.4% and 27.8%, and severe was 2% and 4.8% in males and females, respectively. The prevalence of IDA was 2.6% in males and 4% in females. Mild and moderate ID was significantly higher among females. In conclusion, non-anemic ID, which is known to be common among female athletes, especially in sports requiring leanness, is also highly prevalent among adolescent males playing ball games. Therefore, screening for hemoglobin and sFer is recommended for young athletes of both genders and in all sports.